P300 event-related potentials as diagnostic biomarkers for attention deficit hyperactivity disorder in children - Chuanxue Tan; Chuanxue Tan; Huimin Zhou; Anqi Zheng; Miao Yang; Chunyang Li; Ting Yang; Tingyu Li; Jie Zhang (Frontiers in Psychiatry)
ObjectivesThis study aimed to evaluate the utility of P300 event-related potentials (ERPs) as neurophysiological biomarkers for diagnosing attention deficit hyperactivity disorder (ADHD) and to establish preliminary diagnostic thresholds for their use.MethodsA total of 106 children diagnosed with ADHD and 66 healthy controls were enrolled. Using a visual Oddball paradigm, P300 parameters were recorded at Fz, Cz, and Pz zones. Key metrics analyzed included P300 amplitude and latency as well as reaction time and correct responses. Statistical tests and logistic regression analysis identified significant group differences, while receiver operating characteristic (ROC) analysis determined the diagnostic performance of these parameters.ResultsChildren with ADHD exhibited significantly lower P300 amplitudes and longer latencies across all electrode sites compared to controls. Logistic regression identified Cz amplitude (p = 0.001), Pz amplitude (p = 0.011), maximum reaction time (p = 0.037), and correct response count (p < 0.001) as significant predictors of ADHD. ROC analysis showed that Cz amplitude, Pz amplitude, maximum reaction time, and correct responses achieved AUCs of 0.81, 0.75, 0.72, and 0.86, respectively, with sensitivities ranging from 66% to 80% and specificities from 61% to 95%. These results underscore the diagnostic potential of both electrophysiological and behavioral markers in ADHD assessment.ConclusionsCz and Pz amplitude, maximum reaction time, and correct responses each demonstrated strong diagnostic utility for distinguishing ADHD from typically developing children. The use of these neurophysiological and behavioral indicators as objective complements to traditional clinical assessments.